2010
DOI: 10.2166/aqua.2010.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acid on the oxidation of phenolic endocrine disrupting chemicals by permanganate

Abstract: The effect of dissolved humic acid on the oxidation of phenolic endocrine disrupting chemicals (EDCs) by potassium permanganate was studied. It was found that the degradation of phenolic EDCs is promoted to various extents by the addition of humic acid. Results show that the removal rate of estrone by permanganate within 3 min of reaction time is increased from approximately 10% in control experiments to 68% when 0.08 mg l 21 of humic acid is present in the reaction system. The oxidation experiment of nine typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…In addition, the HA-induced improvement in the oxidation of phenols by permanganate was strongly dependent on the amount and position of chlorine substituents on the aromatic ring. Shao et al also reported that the promotive effects of HA on the oxidation of phenolic EDCs by permanganate were dependent on the structure of EDCs, consistent with our observations. Figure also reveals that the presence of HA slightly decreased the oxidation rate constants of phenols at pH ≥8.0, indicating that HA played a role under alkaline conditions different from that under acidic and/or neutral conditions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the HA-induced improvement in the oxidation of phenols by permanganate was strongly dependent on the amount and position of chlorine substituents on the aromatic ring. Shao et al also reported that the promotive effects of HA on the oxidation of phenolic EDCs by permanganate were dependent on the structure of EDCs, consistent with our observations. Figure also reveals that the presence of HA slightly decreased the oxidation rate constants of phenols at pH ≥8.0, indicating that HA played a role under alkaline conditions different from that under acidic and/or neutral conditions.…”
Section: Resultssupporting
confidence: 92%
“…1 Jiang et al 19,20 also reported that the presence of HA can improve the oxidation of TCS by permanganate at pH 5.0−7.0 and the oxidation of BPA by permanganate at pH <7.0, and the improvement was greater at lower pH. Shao et al 25 confirmed that the presence of HA could facilitate the oxidation of nine EDCs by permanganate at pH 5.8 to different extents, depending on the structure of EDCs. Our previous studies elucidated that the high-molecular weight subunits, carbon− carbon double bonds, π-electrons, and long conjugated bonds in HA contributed to its positive influence on the oxidation of phenol and/or chlorophenol by permanganate.…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…humic acid (HA), phosphate, and EDTA, could accelerate the reaction between phenolic compounds and permanganate [28,35]. It was also confirmed in our previous study that HA could greatly promote the permanganate oxidation of nine kinds of phenolic endocrinedisrupting chemicals over a wide pH range [36]. HA is the major component of natural organic matter (NOM) that consisted up to 90% of DOC in surface waters.…”
Section: The Degradation Of Cps In Real Water Backgroundmentioning
confidence: 55%
“…All these previous studies confirmed that the presence of HA facilitating the formation of in situ MnO 2 contributes to the enhancement of the oxidation of phenols by permanganate. In addition, the promotive effect of HA is not only dependent on pH of the aquatic system but also associated with the structures of phenolic compounds [35,36]. The oxidative ability of the in situ formed MnO 2 decreases with the increase in pH and takes effect for oxidation of phenols by permanganate under acidic and neutral pH conditions, while it decays and even shows no effect under alkaline conditions.…”
Section: The Degradation Of Cps In Real Water Backgroundmentioning
confidence: 99%